Fractional order PDα-type ILC for linear continuous time-delay switched system with disturbance measurement and uncertainties noise - Omprakash Dewangan (Journal of Hyperstructures, 2024)
This study investigates the efficacy of a novel PDα-type fractional-order iterative learning control (FOILC) approach for a class of fractional-order linear continuous-time delaying switched systems. The approach is evaluated in terms of Lp norm performance, aiming to mitigate the challenges associated with time delays in repetitive regulation of fractional-order linear systems. The generalised Young inequality of the convolution integral is used to leverage the resilience of the PDα-type approach in the iteration domain when the systems are perturbed by constrained external disturbances. We next analyse the convergence of the techniques for noise-free systems. The results demonstrate that it is feasible to guarantee both convergence and robustness over the duration of the experiment in certain situations. We study the convergence of error for the proposed class of fractional-order linear continuous-time delaying switched systems.